1999
DOI: 10.1002/(sici)1521-3862(199908)5:4<159::aid-cvde159>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

MOCVD Growth and Characterization of ZrO2 Thin Films Obtained from Unusual Organo-Zirconium Precursors

Abstract: ZrO 2 thin films were deposited on polycrystalline alumina, glass, á100ñ silicon, and stainless steel substrates by metal-organic chemical vapor deposition (MOCVD). Depositions were carried out in a hot wall reactor at reduced pressure (0.6 torr) in the temperature range 400±550 C, using zirconium cyclopentadienyl derivatives as precursors, both in a flux of oxygen and of an oxygen/water vapor mixture. High quality zirconia films with high growth rates were obtained by employing (C 5 H 5 ) 2 Zr(CH 3 ) 2 . Scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…Notably, after the PVA/zirconium oxychloride composite fibres were calcined at 800 C ( Fig. 4(b)), crystalline peak of PVA disappeared, and four reflection peaks corresponding to the pure ZrO 2 crystalline with tetragonal phase [26] appeared at 2y ¼ 30:2 (1 1 1), 35.2 (2 0 0), 50.3 (2 2 0), 60.2 (3 1 1), respectively. Thus, the results clearly showed that the as-prepared product was pure ZrO 2 nanofibres.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, after the PVA/zirconium oxychloride composite fibres were calcined at 800 C ( Fig. 4(b)), crystalline peak of PVA disappeared, and four reflection peaks corresponding to the pure ZrO 2 crystalline with tetragonal phase [26] appeared at 2y ¼ 30:2 (1 1 1), 35.2 (2 0 0), 50.3 (2 2 0), 60.2 (3 1 1), respectively. Thus, the results clearly showed that the as-prepared product was pure ZrO 2 nanofibres.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…On the other hand, zirconia (ZrO 2 ) has attracted much interest recently due to their specific optical and electrical properties [18,19] and potential applications, including transparent optical devices and electrochemical capacitor electrodes [20], oxygen sensors [21], fuel cells [22], catalysts [23] and advanced ceramics [24]. A few methods on the preparation of ZrO 2 nanocrystalline powder, films and nanotube were reported [25][26][27]. However, to our knowledge, there have been no reports on the preparation of ZrO 2 nanofibres.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in the presence of both hydroxylated and bare silicon surface sites, the alkoxide precursor will preferentially bind to the latter, opening a path for uncontrolled reactions leading to contamination. Their main advantage is the higher thermal stability compared to alkylamides and alkoxides, which allows the use of cyclopentadienyls at temperatures above $400 C. 18,[142][143][144][145] The thermal stability and volatility of these compounds have been tuned through a careful modification of the ligands, which has led to a wide range of available cyclopentadienyl-based precursors. 140 As indicated above, the Bohlmann interaction in alkoxides is weaker than in alkylamides and, consequently, stronger C-H bonds are expected.…”
Section: B Surface Reactions Of Hf[n(ch 3 ) 2 ] 4 As An Example Of Mmentioning
confidence: 99%
“…Under practical conditions, the best solution is to decrease the amount of defect sites (i.e., to increase the extent of hydroxylation on the surface), for example, by extending the water pulse during ALD. [145][146][147] Choosing among this myriad of compounds, we will focus on the precursor Hf[CH 3 -C 5 H 4 ] 2 [CH 3 ] 2 , as the combination of cyclopentadienyl and methyl ligands is often used in transition metal deposition, 143 specifically, for deposition of HfO 2 films. Ligand decomposition through scission of the central C-H bond features a kinetic barrier of 115 kJ/mol, almost twice as large as the one observed in the case of Hf alkylamide, which indeed demonstrates that the C-H weakening effect of the heteroatom (O) is less pronounced than in the case of alkylamides.…”
Section: B Surface Reactions Of Hf[n(ch 3 ) 2 ] 4 As An Example Of Mmentioning
confidence: 99%
“…The resulting O 2 /H 2 O mixture was introduced as co-reactant gas very close to the reaction zone to minimize reactions with precursors in homogeneous phase. The water vapor mixed with oxygen is usually employed in the CVD of oxide films for its beneficial effects on the precursor decomposition, since it favours a protolytic cleavage of the Metal-C bond yielding stable organic by-products during the deposition process, thus reducing the carbon contamination within the films (8).…”
Section: Conventional Mocvd Apparatusmentioning
confidence: 99%